"Everything Old Is New Again": A Review of Current Complementary and Alternative Medicine Trends. Issue 6 (November 2021) - Hoffman, Jenni L.
Abstract : Complementary and alternative medicine therapies can be used as adjuvant or preventive therapy, and have newer applications: cryotherapy, halotherapy, floatation therapy, and compression therapy. Nurse practitioners need to know about these therapies and their applicability to patient populations. Appropriate integration of these therapies is part of holistic care, which they strive to provide.